Dual function of rhodium photodeposition on ZnO/ZnS: Enhanced H2 production and photocorrosion suppression in water - Khan, Sovann; Poliukhova, Valeriia; Tamir, Nomin; Park, Jaehyun; Suzuki, Norihiro; Terashima, Chiaki; Katsumata, Ken-Ichi; Cho, So-Hye (Pergamon Press Ltd., 2023)
It is widely known that semiconductors such as ZnO and ZnS tend to be unstable in water-splitting photocatalysis due to self-corrosion by the photogenerated charges under prolonged light irradiation. In this work, we demonstrate that proper engineering of photodeposition of Rh species on ZnO-ZnS heterostructure (ZnO/ZnS) can enhance their photocatalytic activity and secure their stability at the same time. During the Rh photodeposition, both electrons and holes generated on the surface of ZnO/ZnS contributed to the formation of Rh-0 metal and Rh-oxides on its surface. Our results have shown that as little as 0.02 at.% of Rh photodeposition can dramatically increase the activity and reduce self-corrosion of ZnO/ZnS during photocatalytic H-2 production from pure water. The average H-2 production rate of our optimal catalyst was 0.05 at.%. Rh-loaded ZnO/ZnS was similar to 5.31 mmol(-1) g(-1) h(-1), reaching a maximum quantum efficiency of 22.9% at 365 nm. (c) 2022 The Authors. Published by Elsevier Ltd on behalf of Hydrogen Energy Publications LLC. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).